Strongyloides Presenting as an Ulcerated Gastrointestinal Mass and Pulmonary Nodules in a Chronic Alcoholic: A Case Report - Oh, Janice; Gower, Arjan (Archives of Clinical and Medical Case Reports, 2021)
Strongyloidiasis is a parasitic infection of various clinical manifestations by the helminth Strongyloides stercoralis, with immunocompromised patients at higher risk for more severe cases. It is uncommonly seen in the United States, with a majority of patients without symptoms. In immigrant patients of immunocompromised state that initially present with nonspecific clinical manifestations, the inclusion of parasitic infections on the differential is crucial to initiate appropriate treatment as early as possible. We report a case of hyperinfection of Strongyloidiasis, which unusually presented with a gastrointestinal ulcerated mass and pulmonary nodules.